2021
DOI: 10.3390/d13040162
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyte Diversity along an Elevational Gradient on Pico Island (Azores, Portugal)

Abstract: The study of elevational patterns is a valuable method for inferring the influence of the climate and other variables in the regional distributions of species. Bryophytes are ideal for revealing different environmental patterns in elevational studies, since they occur from sea level to above the tree line. Taking advantage of the long elevational transect of Pico Island and the use of standardized survey methods, our main aims were: (1) to identify and characterize the alpha and beta diversities of bryophytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Distribution of species richness along elevational gradients, related to the area of each altitudinal belt, shows a hump-shaped relationship with elevation. This pattern recorded on Mt Etna is in accordance with other studies on bryophytes along elevational gradients on several islands, such as La Réunion [ 12 ], La Palma (Canary Islands) [ 13 ], Pico Island (Azores Islands) [ 14 ], and in the continental transects in Colombia [ 12 ]. Along the 27 altitudinal intervals of the elevation transect on Mt Etna, many species of bryophytes can be observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Distribution of species richness along elevational gradients, related to the area of each altitudinal belt, shows a hump-shaped relationship with elevation. This pattern recorded on Mt Etna is in accordance with other studies on bryophytes along elevational gradients on several islands, such as La Réunion [ 12 ], La Palma (Canary Islands) [ 13 ], Pico Island (Azores Islands) [ 14 ], and in the continental transects in Colombia [ 12 ]. Along the 27 altitudinal intervals of the elevation transect on Mt Etna, many species of bryophytes can be observed.…”
Section: Discussionsupporting
confidence: 91%
“…The many studies to date have focused on relatively few taxonomic groups, in particular vascular plants, invertebrates, and vertebrates [ 11 ]. Research on bryophyte diversity along elevation gradients is mainly focused on large mountains in various parts of the world, including tropical zones, Alps, and central Apennines [ 8 , 11 , 12 , 13 , 14 , 15 ]., while the Mediterranean islands have received no attention.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, the bryophyte species in E4 (1296-1398m) displayed the highest levels of independent distribution among species pairs. Previous studies have demonstrated that altitude can affect niche selection, with certain species exhibiting pronounced growth advantages in high-altitude areas [49] . The strong negative correlation observed in the elevation gradient of E3 (1194-1295m) suggests that the bryophyte community at E3 (1194-1295m) elevation is relatively stable, with most stone walls in this altitude area located in parks with diverse vegetation, similar stone wall types, and minimal environmental impact differences.…”
Section: Discussionmentioning
confidence: 99%
“…Bryophytes are small, possess both simple morphology and anatomy with a dominant haploid life cycle, and are able to disperse either by spores or by vegetative propagules, such as fragments of leaf and thallus or specialized structures with a high regeneration capacity [ 15 , 18 , 19 ]. Bryophytes grow in diverse habitats, such as soil, tree trunks, barks and branches, as well as rock surfaces, and take the mineral nutrients required for their growth directly from the substances dissolved in the moist substrates they live on [ 20 ]. Due to the absence of epidermal cuticles and the high surface-to-volume ratio, bryophytes are highly susceptible to environmental impacts.…”
Section: Spore-bearing Plantsmentioning
confidence: 99%